Perancangan Sistem Informasi Pengelolaan Data Pedagang Menggunakan Metode Prototype pada Pasar Wage - Darmansah, D; Raswini, R (STIKOM Tunas Bangsa Pematangsiantar, 2022)
The Regional Technical Implementation Unit (UPTD) of Pasar Wage in the process of managing trader data is still considered ineffective, because all data processing, especially in the personnel section, is still done manually where in the process of collecting data on traders and managing market retribution, so that they often face problems in their operational activities. This research is designed as a trader data management information system. The system design method used in this report is a prototype model which includes user needs analysis, interface design and website display testing. The research report on designing a website-based trader data management information system using tools or work aids, namely figma. Implementation and testing of the website-based merchant data management information system design describes the specification of website user needs, interface implementation and testing using the User Acceptance Test (UAT). The existence of a computerized website-based trader data management information system design makes it easier for the Wage Market UPTD managers, namely admins, employees and traders to manage and obtain data in the Wage market more quickly and accurately.